Examining the Relationship of Cognitive and Affective Images on Destination Loyalty: A Case of Culture, Adventure, Nature, Food, and Festival Tourism in Sarawak - Ting Ling, Toh (UNIMAS, 2025)
This study investigates the intricate interplay between cognitive and affective images in shaping tourists' destination loyalty, focusing specifically on culture, adventure, nature, food, and festival (CANFF) tourism in Sarawak as elements of cognitive image. In contemporary tourism research, identifying the drivers behind tourists' loyalty toward a specific destination is crucial for sustainable tourism development. The purpose of this study is to examine the impact of destination images on tourists' behavioural intentions. More specifically, this research investigates the relationship between cognitive image and affective image, and the subsequent effects of both cognitive and affective images on tourists' intentions to revisit and recommend the destination. A systematic survey was conducted using convenience sampling of tourists visiting Sarawak, yielding 420 valid responses after data screening. A disjoint two-stage approach in Partial Least Squares Structural Equation Modelling (PLS-SEM), appropriate for testing higher-order constructs (HOCs), was employed in this research. The findings support the conceptualization of a tourist destination's cognitive image as a reflective-formative, multidimensional higher-order construct encompassing culture, adventure, nature, gastronomy, and festivals (CANFF). Collectively, these CANFF attributes significantly contribute to forming Sarawak's cognitive image, illustrating how diverse destination elements coalesce to shape tourists' perceptions and drive their intentions to revisit and recommend Sarawak. Results also indicate a positive influence of cognitive image on affective image, with both cognitive and affective images positively influencing tourists' behavioural intentions. Notably, the affective image exerts a stronger impact on tourists' intentions to revisit and recommend the destination compared to the cognitive image, implying that emotions and feelings are more accurate predictors of behavioural intentions. The implications of this study are twofold. Firstly, it contributes to destination image and loyalty theories by empirically establishing nuanced relationships between cognitive and affective elements. Secondly, it offers practical insights for destination management organizations (DMOs) and policymakers in Sarawak and elsewhere to develop targeted strategies that enhance both cognitive and affective aspects of the destination experience, thereby fostering greater tourist loyalty. Leveraging these insights, Sarawak can progress toward its goal of becoming a leading tourist destination, significantly contributing to its economic development by 2030.